G31(P) Reducing the trauma of lumbar punctures using simulation. (May 2019) - Watterson, C; Mallett, P; Taylor, M; Bourke, T
Abstract : Aims: The objective of this quality improvement project was to increase CSF interpretability by 50% in a 5 month period using an Lumbar Puncture (LP) simulator to enhance trainee technique. LP is a core practical procedure of level 1 RCPCH training. Lack of opportunity, experience and low procedural confidence can make it difficult to achieve this competency. Traumatic punctures causing blood stained CSF can lead to difficulties with interpretation. Methods: Prospective data was collected during August 2017 to December 2017 for general paediatric admissions (patient demographics, trainee grade, number of attempts, microscopy results and interpretability). Three half-day simulated procedural training days practicing LP technique, discussing appropriate sedation and clinical cases occurred during this time and their impact was measured. Results: 58 LPs were performed during the study period. Participation of junior trainees increased from 8% to 40% in the first 4 months but then decreased to 15% in December. Encouragingly after the second LP course CSF interpretability increased from 47% to 92%. LPs carried out in theatre under general anaesthetic (4 patients) were mostly atraumatic (RBC 0–23). The number of LP attempts also impacted on CSF quality and likelihood of achieving interpretable CSF microscopy Conclusions: Simulation-based training is beneficial for trainees to gain experience of procedural skills. This project shows that when trainees are given the opportunity to gain hands-on experience using high-fidelity models it translates to enhanced user confidence, willingness to participate in the clinical setting and increased procedural competence (table 1 ). During the 5 months CSF interpretability increased from 47% to 69%, nearly achieving our overall project aim.